Taking the road less traveled – the therapeutic potential of CBP/β-catenin antagonists. (2nd September 2021) - Kahn, Michael
ABSTRACT: Successfully targeting aberrant Wnt signaling in cancer, and even more so in chronic diseases, requires a fine balancing act, wherein the 'dark side' of Wnt signaling in disease can be abrogated without interfering with the crucial roles of Wnt signaling in normal tissue homeostasis and repair. Our identification of small molecule CBP/β-Catenin antagonists revealed (a) the distinctive roles that the Kat3 coactivators CBP and p300 play in Wnt signaling and orchestrating critical cellular decisions, and (b) their therapeutic potential. Areas covered: This perspective discusses the challenges of targeting the Wnt signaling cascade, the safety, efficacy, and therapeutic potential of specific CBP/β-catenin antagonists and a rationale for the pleiotropic effects of CBP/β-catenin antagonists beyond Wnt signaling. Expert opinion: CBP/β-catenin antagonists can correct lineage infidelity, enhance wound healing, both normal and aberrant (e.g. fibrosis) and force the differentiation and lineage commitment of stem cells and cancer stem cells by regulating enhancer and super-enhancer coactivator occupancy. Small molecule CBP/β-catenin antagonists rebalance the equilibrium between CBP/β-catenin versus p300/β-catenin dependent transcription and may be able to treat or prevent many diseases of aging, via maintenance of our somatic stem cell pool, and regulating mitochondrial function and metabolism involved in differentiation and immune cell function.